Defining Sustainability Criteria in Project Design - A Case Study of the Olympic Dam Expansion - I Cawrse; H Bateman; G Carnes; S Cawrse (The Australasian Institute of Mining and Metallurgy, 2009)
In developing mineral resources, the focus typically centres on the management of identified social and environmental impacts and compliance with regulatory requirements. However, opportunities to protect and enhance the environment and communities are most effective in the planning and design phases. Achieving the objective of integrating sustainability considerations as an element of design decision making requires that the design criteria be technically sound, relevant to the project and applicable to desired design outcomes. This is particularly important for projects employing virtual teaming, where design engineers may be geographically dispersed and are unlikely to be familiar with site specific sustainability challenges and opportunities. This paper documents the approach taken by BHP Billiton to incorporate sustainability principles, objectives and guidelines in design criteria for the Olympic Dam Expansion (ODX) project. It describes the range of inputs used in defining sustainability objectives which interface in a framework that is dynamic and transferable to other mining projects and to engineering design in general. The Sustainability in Design Criteria document distils statutory requirements, corporate standards, lessons learned and leading industry practice into a single coherent framework that supports engineers to approach problem solving as a holistic and integrated exercise with a long term perspective. The framework also serves to improve linkages between internal stakeholders by fostering greater communication, collaboration and innovation to deliver more sustainable outcomes through the design process.